2020
DOI: 10.30892/gtg.32420-576
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Sociodemographic Aspects, Satisfaction and Loyalty in Gastronomic Festivals

Abstract: Currently, the organization of gastronomic festivals is an opportunity to rescue the culture and development of a destination. The present study was carried out in the city of Naranjal, Ecuador at the "Gastronomic Festival of the Red Crab" and its objectiv es are: (i) to identify the relationship between the level of education and income, as sociodemographic variables as well as the level of satisfactio n of people attending a Gastronomic Festival. (ii) identify the influence of Satisfaction on the probability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Gastronomy is an important option for choosing and exploring a place to visit. Because it is a pillar of the destination's cultural heritage (Esparza et al, 2022) and an excellent source of attraction (Carvache et al, 2020).…”
Section: Gastronomy Experience and Satisfactionmentioning
confidence: 99%
“…Gastronomy is an important option for choosing and exploring a place to visit. Because it is a pillar of the destination's cultural heritage (Esparza et al, 2022) and an excellent source of attraction (Carvache et al, 2020).…”
Section: Gastronomy Experience and Satisfactionmentioning
confidence: 99%
“…Ignatov and Smith (2006) identified that the experience with gastronomy at a destination could represent a valuable source of satisfaction for tourists, and this is why gastronomy is increasingly linked to the search for new experiences through a visit to the traditions and culture of a particular destination (Hendijani, 2016). This is why gastronomy is an integral part of the traveller’s behaviour (Carvache-Franco et al , 2021).…”
Section: Bibliographic Reviewmentioning
confidence: 99%
“…The culinary experience in the destination may represent a significant source of satisfaction for tourists (Hendijani, 2016). Carvache-Franco et al (2021) indicate that gastronomy is a great attractions in a trip; modern tourists appreciate the traditional food cooked in a burner or wood-burning stoves, the cultural roots and the symbolism of a culinary expression. At the same time, Erkmen (2019) showed evidence of the positive effect of the local food on the satisfaction with the destination.…”
Section: Bibliographic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…wine festivals). In the framework of the above, they have pointed out that in order to meet the needs of tourists, a complex package is required (Fusté-Forné, 2019; López-Guzmán, 2019), which includes, in addition to the presentation of region's wine offering, also the organisation of gastronomic type events (Carvache-Franco et al, 2020;Komariah et al, 2020). The fourth major topic concerns wine tourism and sustainability (Andrade-Suárez and Caamaño-Franco, 2020; Baird et al, 2018;Karagiannis and Metaxas, 2020), in which researchers draw attention to two things: they emphasise the need to use environmentally friendly technologies in the product ion of grapes, and to minimise the damage to nature through the environmental loads caused by tourists.…”
Section: Literature Reviewmentioning
confidence: 99%